Pregnant and non-pregnant women and low back pain-related differences on postural control measures during different balance tasks - Carvalho, Adriana Paula Fontana; Dufresne, Sébastien S.; Oliveira, Márcio Rogério de; Beraldo, Fernanda Kelly Sereniski; Souza, Pablo Eduardo Albuquerque de; Silva, Rubia Stella da; Dubois, Maryane; Dallaire, Mathieu; Ngomo, Suzy; Jr, Rubens Alexandre da Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Introduction: Low back pain (LBP) is the most common musculoskeletal complaint in pregnancy, being responsible for many negative impacts. Objective: To evaluate the effect of LBP on static and dynamic balance in pregnant women and whether pregnancy mediates the results compared to non-pregnant women. Methods: 44 women (mean age 30 yrs) participated voluntarily in this study: 16 pregnant women with LBP starting in pregnancy, 14 pregnant women without LBP and 14 non-pregnant women as a group control. Participants were assessed for static postural balance using a force platform and dynamic mobility balance using the Timed Up and Go (TUG) test. Results: The pregnant women with LBP showed significant (P < 0.04, for mean, d= 1,2) poor postural balance in static tests (force platform), in the area of COP eyes open. In dynamic balance (TUG test), statistical difference was found between the groups (P 0.038) and the effect size were moderate to strong in the comparison between the three groups. The most sensitive differences were reported mainly between pregnant women with LBP versus non-pregnant control group in balance measures from force platform. Conclusion: The findings indicate that LBP associated to pregnant clinical status can decrease the balance capacity in women. These results have implication for balance evaluation and retraining in pregnant women with and without LBP from rehabilitation or prevention programs.